2023
DOI: 10.5829/ije.2023.36.03c.17
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium of Ammonia (NH3) and Ammonium (NH4+) during Microalgae Harvesting using Electrocoagulation

Abstract: Harvesting microalgae is an important process in gaining biomass while the remaining water is still rich in nutrients. These nutrients, mainly nitrogen and phosphorous, could cause eutrophication of water bodies (rivers, lakes, and oceans) and ecosystem degradation if discharged directly without proper treatment. Electrocoagulation (EC) is one of the harvesting methods and has several advantages: ease of operation, fast harvesting, adaptability, environmental friendliness, and low footprint. However, EC method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Higher pH and temperature values favor the formation of toxic molecular ammonia. Moreover, higher pH values result in more ionized ammonia, which raises toxicity (Purwono et al, 2017). The clinoptilolite used in this research can effectively adsorb NH4 from water.…”
Section: Discussionmentioning
confidence: 99%
“…Higher pH and temperature values favor the formation of toxic molecular ammonia. Moreover, higher pH values result in more ionized ammonia, which raises toxicity (Purwono et al, 2017). The clinoptilolite used in this research can effectively adsorb NH4 from water.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was reported that the results obtained from the Nessler method were similar and reliable to the results obtained from the traditional electrode method (Prajapati, 2014). The ammonia and TAN were calculated as given below (Purwono et al, 2017):…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, based on previous research (Rinquest et al, 2019;Williams et al, 2019), it is expected that 80-90% of a processing plant's total water use will be discharged as poultry slaughterhouse wastewater (PSW), consuming an average of 26.5 L per processed bird (Fatima et al, 2021). Ionized ammonia (N 4 + ) and free ammonia (NH 3 ) are the two forms of reduced inorganic nitrogen found in the aqueous medium, which can exist in water as ammonia gas or as water soluble ammonia ions (Purwono et al, 2023). The majority of phosphorus in natural water and wastewater , and PO 4 3that originates from poultry manure, meat, and bone meal (Topcu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%